2020
DOI: 10.1089/cap.2019.0161
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Efficacy and Tolerability of Topiramate for Tic Disorders: A Meta-Analysis

Abstract: Background: Tic disorders (TDs) are chronic neuropsychiatric disorders that usually begin in childhood. Currently, antipsychotic drugs, such as aripiprazole and risperidone, are frequently used to treat TD. However, adverse reactions limit their further usage. The efficacy of topiramate has been reported in recent studies. This study aimed to investigate the efficacy and tolerability of topiramate in the treatment of children with TDs. Methods: In this study, we performed a meta-analysis to assess the efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…We ultimately included 14 NMAs and 90 MAs, reporting on 15 disorders or groups of disorders. For ADHD, we included three NMAs 5,20,21 and 21 MAs 22‐42 ; for autism, one NMA 43 and 21 MAs 12,44‐63 (including one focusing on comorbid anxiety disorders and autism) 12 ; for depressive disorders, two NMA 7,10 and seven MAs 64‐70 ; for obsessive‐compulsive disorder, one NMA 71 and six MAs 72‐77 ; for anxiety disorders, two NMAs 11,78 and five MAs 12,79‐82 (plus two MAs specific on social anxiety disorder 83,84 ); for enuresis, one NMA 85 and six MAs 86‐91 , for disruptive behavior/dissocial/conduct disorders, five MAs 92‐96 (plus one focusing on youth with comorbid ADHD) 25 ; for eating disorders, one NMA 97 and four MAs 98‐101 ; for schizophrenia spectrum disorders, three NMAs 8,102,103 and two MAs 104,105 ; for bipolar disorder, four MAs 106‐109 ; for tic disorder, two MAs 110,111 ; for Tourette's disorder, two MAs 112,113 ; for encopresis, two MAs 114,115 ; for developmental coordination disorder, one MA 116 ; and for PTSD, one MA 117 .…”
Section: Resultsmentioning
confidence: 99%
“…We ultimately included 14 NMAs and 90 MAs, reporting on 15 disorders or groups of disorders. For ADHD, we included three NMAs 5,20,21 and 21 MAs 22‐42 ; for autism, one NMA 43 and 21 MAs 12,44‐63 (including one focusing on comorbid anxiety disorders and autism) 12 ; for depressive disorders, two NMA 7,10 and seven MAs 64‐70 ; for obsessive‐compulsive disorder, one NMA 71 and six MAs 72‐77 ; for anxiety disorders, two NMAs 11,78 and five MAs 12,79‐82 (plus two MAs specific on social anxiety disorder 83,84 ); for enuresis, one NMA 85 and six MAs 86‐91 , for disruptive behavior/dissocial/conduct disorders, five MAs 92‐96 (plus one focusing on youth with comorbid ADHD) 25 ; for eating disorders, one NMA 97 and four MAs 98‐101 ; for schizophrenia spectrum disorders, three NMAs 8,102,103 and two MAs 104,105 ; for bipolar disorder, four MAs 106‐109 ; for tic disorder, two MAs 110,111 ; for Tourette's disorder, two MAs 112,113 ; for encopresis, two MAs 114,115 ; for developmental coordination disorder, one MA 116 ; and for PTSD, one MA 117 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we checked the references since 2011 of other systematic reviews/metaanalyses [5][6][7][8][9], existing guidelines [3,4,[10][11][12], nonsystematic reviews on TS with statements about pharmacological treatment, i.e., dealing with various agents or mentioning treatment in their title . In addition, we had a look into the references of agentspecific reviews and meta-analyses of (in alphabetical order) aripiprazole [65][66][67][68][69][70][71][72], atypical antipsychotics [73], botulinum toxin [74][75][76][77][78][79][80][81][82][83][84][85], cannabis [86][87][88], clonidine [89,90], complementary alternative medicine [91], deutetrabenazine [92], non-dopaminergic agents [93], traditional Chinese medicine [94], and topiramate [95,96]. Moreover, we screened references of reviews on specific aspects of TS if they describe treatment options for coexisting attention deficit hyperactivity disorder (ADHD) [97]…”
Section: Methodology Of Selection Of Agents and Literature Search Strategymentioning
confidence: 99%
“…There have been no new English-language RCTs, since a 12-week randomized controlled trial of topiramate versus placebo published in 2010 that showed superior effects of topiramate compared to placebo in 29 children and adults with TS [ 164 ]. However, the authors of a recent meta-analysis [ 96 ] summarizing a total of 15 studies from China involving 1070 participants aged 2–17 years concluded that topiramate is a promising medication with good efficacy and tolerability for children with TS compared to haloperidol and tiapride.…”
Section: Other Agentsmentioning
confidence: 99%
“…In a study of 49 pediatric patients with tic disorders(TDs) treated with tiapride showed that the symptoms improved in 83.3% of the patients [ 13 ]. However, a meta-analysis, which included 14 studies evaluating the efficacy of topiramate for the treatment of TDs, reported that compared with haloperidol and tiapride, topiramate appears to be a promising medication with good efficacy and tolerability for children with TDs [ 14 ]. Our sample also demonstrated significantly lowered impairment scores in TPM than tiapride did after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Topiramate is a sulfamate-modified fructose diacetonide, but its mechanisms of action are still unknown. Yu et al [ 14 ] showed that topiramate is a promising medication with good efficacy and tolerability for children with TDs, compared with haloperidol and tiapride. The most common side effects for topiramate are language problems, cognitive disorders, kidney stones, and weight loss.…”
Section: Discussionmentioning
confidence: 99%